Impact of Cannabis Legalization on Umbilical Cord Tissue Tetrahydrocannabinol Levels - Spence, Kimberly; Milota, Sarah; Buchanan, Paula; Acharya, Nirja; Mathur, Amit M. (American Journal of Perinatology, 2024)
This study aimed to assess the impact of cannabis legalization on both qualitative and quantitative umbilical cord tissue tetrahydrocannabinol (THC) rates and concentrations as a proxy for fetal exposure.This is a retrospective, observational study of umbilical cord tissue THC levels in a single center, comparing THC exposure rates and concentration levels before and after cannabis legalization in the state of Illinois, Epoch 1 (October 1, 2018–June 30, 2019, pre-legalization) and Epoch 2 (July 1, 2019–August 31, 2021, post-legalization).A total of 811 umbilical cords were analyzed during epoch 1 and 2,170 during epoch 2. A higher percentage of umbilical cord tissue tested positive for THC in Epoch 2 compared with Epoch 1 (46.2 vs. 40.6%; p < 0.01). Mean THC levels were 51% higher in umbilical cord tissue in Epoch 2 versus Epoch 1 (6.2 ng/g vs. 4.1 ng/g; p < 0.001).Legalization of recreational cannabis was associated with more fetuses exposed to THC and in higher concentrations.
Keywords: cannabis; umbilical cord; tetrahydrocannabinol